Interplane corrugations in quasi-one-dimensional Fermi surface sections of deuterated and undeuterated kappa-(BEDT-TTF)(2)Cu(NCS)(2) - Narduzzo, A; Edwards, R; Ardavan, A; Singleton, J (2003)
Recently a small but definite isotope effect has been found on deuteration of the organic superconductor kappa-(BEDT-TTF)(2)Cu(NCS)(2) [Physica C 351 (2000) 251]. We have investigated the alterations in band-structure brought about by deuteration using a millimetre-wave technique which is sensitive to the corrugations of the quasi-one-dimensional (Q1D) sheets of the Fermi surface [J. Phys. 13 (2001) 2235]. We have mapped the interplane corrugations of the Q1D Fermi surface sections and discuss the dependence of the warping components of these Q1D sheets on the deuteration. (C) 2002 Elsevier Science B.V. All rights reserved.